Fortification of Beer with Extracts of the Selected Czech Medicinal Herbs and Plants - Helena Pluháčková; Tomáš Gregor; Rastislav Boško; Sylvie Běláková; Zdeněk Svoboda; Karolína Benešová (Kvasný průmysl, 2020)
This study investigated the possibilities of fortification of beer with various herbal extracts. The aim was to fortify beer with natural substances that have favourable effects on consumers´ health. The tested beers were enriched with ethanol extracts of medicinal herbs (ribwort plantain, small leaved linden, purple coneflower, chamomile, sage) so that the sensory characters of the supplemented herbal extract created only an accompanying perception and the malt and hop flavour of beer was preserved. In the enriched beers, the contents of the selected phenolic substances and important essential oils were determined and sensory evaluation was performed. The content of phenolic substances increased the most in beer with linden (42.46 mg/l) and plantain (37.5 mg/l) extracts, approximately four times compared to the original beer (8.11 mg/l). Beer with sage and chamomile extract achieved the best sensory assessment, with components of essential oils added in units of ng/l of beer.